Effectiveness, Safety, and Acceptability of Primaquine Mass Drug Administration in Low-Endemicity Areas in Southern Thailand: Proof-of-Concept Study - Jaranit Kaewkungwal; Wanlapa Roobsoong; Saranath Lawpoolsri; Wang Nguitragool; Suwich Thammapalo; Pathomporn Prikchoo; Amnat Khamsiriwatchara; Rungrawee Pawarana; Pawinee Jarujareet; Daniel M Parker; Piyarat Sripoorote; Mondha Kengganpanich; et al. (JMIR Publications, 2024)
BackgroundA challenge in achieving the malaria-elimination target in the Greater Mekong Subregion, including Thailand, is the predominance of Plasmodium vivax malaria, which has shown extreme resilience to control measures. ObjectiveThis proof-of-concept study aimed to provide evidence for implementing primaquine mass drug administration (pMDA) as a strategy for P. vivax elimination in low-endemicity settings. MethodsThe study employed a mixed-methods trial to thoroughly evaluate the effectiveness, safety, acceptability, and community engagement of pMDA. The quantitative part was designed as a 2-period cluster-crossover randomized controlled trial. The intervention was pMDA augmented to the national prevention and control standards with directly observed treatment (DOT) by village health volunteers. The qualitative part employed in-depth interviews and brainstorming discussions. The study involved 7 clusters in 2 districts of 2 southern provinces in Thailand with persistently low P. vivax transmission. In the quantitative part, 5 cross-sectional blood surveys were conducted in both the pMDA and control groups before and 3 months after pMDA. The effectiveness of pMDA was determined by comparing the proportions of P. vivax infections per 1000 population between the 2 groups, with a multilevel zero-inflated negative binomial model adjusted for cluster and time as covariates and the interaction. The safety data comprised adverse events after drug administration. Thematic content analysis was used to assess the acceptability and engagement of stakeholders. ResultsIn the pre-pMDA period, the proportions of P. vivax infections in the pMDA (n=1536) and control (n=1577) groups were 13.0 (95% CI 8.2-20.4) and 12.0 (95% CI 7.5-19.1), respectively. At month 3 post-pMDA, these proportions in the pMDA (n=1430) and control (n=1420) groups were 8.4 (95% CI 4.6-15.1) and 5.6 (95% CI 2.6-11.5), respectively. No statistically significant differences were found between the groups. The number of malaria cases reduced in all clusters in both groups, and thus, the impact of pMDA was inconclusive. There were no major safety concerns. Acceptance among the study participants and public health care providers at local and national levels was high, and they believed that pMDA had boosted awareness in the community. ConclusionspMDA was associated with high adherence, safety, and tolerability, but it may not significantly impact P. vivax transmission. As this was a proof-of-concept study, we decided not to scale up the intervention with larger clusters and samples. An alternative approach involving a targeted primaquine treatment strategy with primaquine and DOT is currently being implemented. We experienced success regarding effective health care workforces at point-of-care centers, effective collaborations in the community, and commitment from authorities at local and national levels. Our efforts boosted the acceptability of the malaria-elimination initiative. Community engagement is recommended to achieve elimination targets. Trial RegistrationThai Clinical Trials Registry TCTR20190806004; https://www.thaiclinicaltrials.org/show/TCTR20190806004